In Vitro Evaluation of the Effect of Scanning Strategy on the Accuracy of Intraoral Scanners - Ghadirifard, Mohammad; Eisaei, Mitra; Hakimaneh, Sayed Mohammadreza; Bafandeh, Mohammad Amin; Shayegh, Sayed Shojaedin (Galen Medical Journal, 2024)
Background: The accuracy of intraoral scanners depends on the scanning strategy, but evidence on how these strategies affect trueness and precision across scanners is limited. Identifying optimal strategies is key to improving performance and clinical outcomes. Materials and Methods: A dental cast obtained from an impression of a fully-dentate patient was initially scanned by a laboratory scanner and then by three intraoral scanners namely Trios®4, Carestream 3800, and Medit i700 with three different scanning strategies of A (occlusal surfaces from the left end to the right end, followed by lingual and then buccal surfaces), B (buccal surfaces followed by occlusal and then lingual surfaces from left to right), and C (continuous labiolingual movement with left-to-right direction). Scans were converted to STL format and analyzed in Geomagic for trueness and precision (ISO 5725-1) using ANOVA, Tukey, Welch, and Games-Howell tests (alpha = 0.05). Results: The effect of scanning strategy was significant on trueness of Carestream (P=0.002) but not Medit and Trios4 (P>0.05). In Carestream, the trueness of strategy A was significantly higher than B (P=0.001). The effect of scanning strategy was significant on precision of Medit (P<0.001) but not Carestream and Trios4 (P>0.05). In Medit, the precision of strategy B was significantly lower than A and C (P<0.001 for both). Conclusion: The scanning strategy’s effect on accuracy varied by scanner type. Strategy A was most accurate in Carestream, while strategy B showed the lowest precision in Medit i700. Other scanners and strategies had similar precision.